1994
DOI: 10.1210/en.135.1.262
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of expression of the genes for steroidogenic enzymes P450 side- chain cleavage, 3 beta-hydroxysteroid dehydrogenase, P450 17 alpha- hydroxylase/C17-20 lyase, and P450 aromatase in fetal mouse gonads

Abstract: It is well known that fetal androgens are required for male sexual differentiation, and it is thought that fetal ovaries are not steroidogenically active. However, molecular details, such as which steroidogenic enzymes are present in fetal testes and which enzymes are absent in fetal ovaries, have not been established. The pattern of expression of the genes that encode four of the steroidogenic enzymes necessary for androgen and estrogen production was examined during fetal development in mouse gonads. Messeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 0 publications
1
69
2
Order By: Relevance
“…Thus, Habert and colleagues have shown that homozygous inactivation of ERB increased the number of gonocytes by 50% in mice at 2 and 6 dpp due to an increase in the proliferation and decrease in apoptosis (Delbès et al 2004). Indeed, there are few data dealing with the production of estrogen in fetal and neonatal rodent testis (Habert & Picon 1984, Greco & Payne 1994, RouillerFabre et al 1998, Delbès et al 2004. These studies indicated that aromatase is expressed in Sertoli cells of fetal testis after the period of gonocyte proliferation (Greco & Payne 1994, Rouiller-Fabre et al 1998, which may explain no alterations in the Nv of gonocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Habert and colleagues have shown that homozygous inactivation of ERB increased the number of gonocytes by 50% in mice at 2 and 6 dpp due to an increase in the proliferation and decrease in apoptosis (Delbès et al 2004). Indeed, there are few data dealing with the production of estrogen in fetal and neonatal rodent testis (Habert & Picon 1984, Greco & Payne 1994, RouillerFabre et al 1998, Delbès et al 2004. These studies indicated that aromatase is expressed in Sertoli cells of fetal testis after the period of gonocyte proliferation (Greco & Payne 1994, Rouiller-Fabre et al 1998, which may explain no alterations in the Nv of gonocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are few data dealing with the production of estrogen in fetal and neonatal rodent testis (Habert & Picon 1984, Greco & Payne 1994, RouillerFabre et al 1998, Delbès et al 2004. These studies indicated that aromatase is expressed in Sertoli cells of fetal testis after the period of gonocyte proliferation (Greco & Payne 1994, Rouiller-Fabre et al 1998, which may explain no alterations in the Nv of gonocytes. However, our data indicate that postnatal aromatase activity probably was affected by MO.…”
Section: Discussionmentioning
confidence: 99%
“…In many species, ovaries acquire the enzymatic capacity to produce estrogen during embryonic life as determined by the capacity of fetal ovaries to convert radiolabeled androgen to estrone and estradiol [6][7][8] or by the amplification of aromatase cDNA by PCR [9]. Aromatase expression in fetal ovaries is extremely low; although it can be increased by treatment with an analog of cAMP but not by follicle stimulating hormone (FSH) [8,10].…”
Section: Fetal Ovariesmentioning
confidence: 99%
“…In the mouse, aromatase expression starts after birth, when the ovary is already well differentiated (Greco and Payne, 1994), whereas Foxl2 expression begins as early as 13.5 dpc in the developing female gonads (Loffler et al, 2003, Pannetier et al, 2003. On the other hand, FoxL2 in the red-eared slider turtle is up-regulated at the female promoting temperature in the differentiating gonads during the temperature sensitive period (TSD; Loffler et al, 2003), whereas no dimorphism in aromatase expression in the adrenal-kidney-gonad complex has been found at female or male promoting temperature during the TSD (Murdock and Wibbels, 2003).…”
Section: Foxl2 and Ovarian Differentiation In Chickenmentioning
confidence: 99%